Confucian and Christian Models of Imitation: A Comparative Case-Study of Yang Xiong's Fayan and John Chrysostom's De laudibus sancti Pauli apostoli. - Hosle, Paul K. (Dao: A Journal of Comparative Philosophy, 2025)
The imitation of exemplars is a fundamental component of moral formation in premodern cultures. This essay compares the reflections on imitation found in Han 漢-dynasty Confucian thinker Yang Xiong's 揚雄 Fayan 法言 (Exemplary Sayings) and late antique Christian preacher John Chrysostom's seven homilies De laudibus sancti Pauli apostoli (On the Praises of St. Paul the Apostle). I analyze how each body of work respectively answers the questions of what constitutes imitation, what characterizes the virtuous exemplar(s), how feasible it is to imitate them, what should motivate us to imitate them, and whether the exemplar is the ultimate standard of morality. While attuned to each figure's own cultural and intellectual context, impressive overlap will be noted not only in the questions with which they engage but also in the answers that they provide. It is hoped that this concrete comparative case-study may not only foster discussion on the relationship between Confucian and Christian ethics but also help in laying the groundwork for a conceptual apparatus by which to approach and understand other models of imitation in their diverse cultural manifestations.